Application de la méthode QuickScan aux biens culturels non muséaux - Inés Flores-Fernández (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This research aims to apply and evaluate the effectiveness of the QuiskScan method on the ecclesiastical assets of the Parish of Santo Domingo in Sanlúcar de Barrameda (Cádiz, Spain). The objectives are to test the viability of the method in a non-museum environment, assess the loss of value through a global evaluation of the different typologies present in the parish and determine which are more vulnerable to the identified risks. Using the risk analysis methodology applied in museums, an Excel matrix is used to assign values and assess vulnerability to agents of deterioration, the result of which is to determine the level of risk and whether this methodology is effective in assessing as another agent the ‘cult function’ they perform, which is crucial for this category of property.